Quantitative diagnostic imaging of cancer tissues by using phosphor-integrated dots with ultra-high brightness - Kohsuke Gonda (Nature Portfolio, 2017)
Abstract The quantitative sensitivity and dynamic range of conventional immunohistochemistry (IHC) with 3,3′-diaminobenzidine (IHC-DAB) used in pathological diagnosis in hospitals are poor, because enzyme activity can affect the IHC-DAB chromogenic reaction. Although fluorescent IHC can effectively increase the quantitative sensitivity of conventional IHC, tissue autofluorescence interferes with the sensitivity. Here, we created new fluorescent nanoparticles called phosphor-integrated dots (PIDs). PIDs have 100-fold greater brightness and a more than 300-fold greater dynamic range than those of commercially available fluorescent nanoparticles, quantum dots, whose fluorescence intensity is comparable to tissue autofluorescence. Additionally, a newly developed image-processing method enabled the calculation of the PID particle number in the obtained image. To quantify the sensitivity of IHC using PIDs (IHC-PIDs), the IHC-PIDs method was compared with fluorescence-activated cell sorting (FACS), a method well suited for evaluating total protein amount, and the two values exhibited strong correlation (R = 0.94). We next applied IHC-PIDs to categorize the response to molecular target-based drug therapy in breast cancer patients. The results suggested that the PID particle number estimated by IHC-PIDs of breast cancer tissues obtained from biopsy before chemotherapy can provide a score for predicting the therapeutic effect of the human epidermal growth factor receptor 2-targeted drug trastuzumab.